Sociedade de risco: possibilidades de articulação da ciência, tecnologia e sociedade com a educação técnica integrada ao ensino médio - João, Plínio Gabriel (Universidade Federal de São Carlos, 2024)
This thesis aims to investigate the possibilities of articulation between Science, Technology and Society (STS) and Technical Education Integrated into High School (ETIM), considering the availability and capacity of teachers, aiming at the formation of critical and autonomous citizens in the risk society. Based on authors such as Beck and Giddens, the research explores the need to adapt to social complexity, analyzing the impact of digital technologies, the importance of ethics and organizational citizenship, and the challenges of education in the information age. The research addresses the dimensions of sustainability proposed by Sachs (2004) and the Sustainable Development Goals (SDGs) of the UN 2030 Agenda, contextualizing them in the reality of ETIM. It examines educational reforms in High School, teacher training and the application of active methodologies, such as Problem-Based Learning (PBL), to promote critical thinking and problem solving. The qualitative methodology, with elements of action research and ethnographic observation, includes an account of experience in technical schools, analyzing the reality of the classroom, the interactions between teachers and students, and the challenges faced by teachers in the implementation of STS. The research concludes that the integration of STS in ETIM is fundamental for the formation of conscious citizens engaged in building a more just and sustainable future, demanding investments in teacher training, infrastructure and adequate teaching materials.
Risk society: possibilities of articulation of science, technology and society with technical education integrated into high school
Sociedad de riesgo: posibilidades de articulación de la ciencia, la tecnología y la sociedad con la educación técnica integrada a la enseñanza media
Keywords: Ciência, Tecnologia e Sociedade; Sociedade de risco; Educação técnica integrada ao ensino médio; Science, Technology and Society; Risk society; Technical education integrated into high school; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE SISTEMAS EDUCACIONAIS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::PLANEJAMENTO EM CIENCIA E TECNOLOGIA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM